Biblical Counseling Personal and Emotional Issues - Clinton, Timothy E; Hawkins, Ronald E. (Grand Rapids Baker Books, 2009)
Hurting people need help. But sometimes those who are faced with helping the hurting could use a little more information about the problems that needy people bring to them. The Quick-Reference Guide to Biblical Counseling provides the answers. It is an
Keywords: Bible -- Psychology -- Handbooks, manuals, etc. Bible -- Use -- Handbooks, manuals, etc. Counseling -- Religious aspects -- Christianity -- Handbooks, manuals, etc